DEVELOPMENT MEDICAL RECORDS MANAGEMENT INFORMATION SYSTEM WITH COMPUTER SUPPORT - Moelijo Slamet Hartono; Djoko Harmantyo., DR, MSc Djoko Harmantyo., DR, MSc (Jurnal Sistem Informasi, 1990)
Lately, the public increasingly critical in obtaining health services especially medical malpracticeoccurred several times. To provide quality health services as desired so many hospital patientsbegan to implement the management system with good medical record. Other parties such asgovernments and scientists already feel the usefulness. And to provide quality medical recordsthe desired information it needs to make a design of the development of medical recordmanagement information system with computer support.At several stages of research methods conducted tahapanpengumpulan activities include data,data processing phases and stages of data analysis. From the analysis carried out on the oldsystem then it can be seen that there are weaknesses so far. With the results of this analysis it canbe designed and evaluated systems globally. After that created a detailed design that includesalso the design of input forms, forms reports, the file structure and specifications program.